The influence of health literacy, social media exposure, and peer influence on vaccine hesitancy among Malaysian youth - Mohamad Arrif Emir, Widad Emir; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study examines the influence of health literacy, social media exposure, and peer influence on vaccine hesitancy among Malaysian youth. A sample of 425 participants, aged 18-30, was surveyed using validated instruments to measure these variables. Pearson correlation and multiple regression analyses were used to assess the relationships between the independent variables and vaccine hesitancy. The findings revealed that health literacy was the strongest negative predictor of vaccine hesitancy, indicating that youth with higher health literacy levels were less likely to resist vaccines. Social media exposure significantly increased vaccine hesitancy, supporting previous findings that misinformation spread via social media platforms fuels distrust toward vaccines. Peer influence also contributed to vaccine hesitancy, demonstrating the substantial impact of social networks on health decision-making. These results underscore the importance of enhancing health literacy, counteracting misinformation on social media, and addressing peer group dynamics in strategies to reduce vaccine hesitancy among Malaysian youth. Health policymakers and public health programs should focus on these key areas to improve vaccine uptake in this population.